Expression of Enzymatically Active Rabbit Hemorrhagic Disease Virus RNA-Dependent RNA Polymerase in Escherichia coli - Vázquez, Ana López (American Society for Microbiology, 1998)
The rabbit hemorrhagic disease virus (RHDV) (isolate AST/89) RNA-dependent RNA-polymerase (3D(pol)) coding region was expressed in Escherichia coli by using a glutathione S-transferase-based vector, which allowed milligram purification of a homogeneous enzyme with an expected molecular mass of about 58 kDa. The recombinant polypeptide exhibited rifampin- and actinomycin D-resistant, poly(A)-dependent poly(U) polymerase. The enzyme also showed RNA polymerase activity in in vitro reactions with synthetic RHDV subgenomic RNA in the presence or absence of an oligo(U) primer. Template-size products were synthesized in the oligo(U)-primed reactions, whereas in the absence of added primer, RNA products up to twice the length of the template were made. The double-length RNA products were double stranded and hybridized to both positive- and negative-sense probes.